The Influence of Market Value and Leverage on IDX Manufacturing Share Prices 2019-2023 - Maulidin T. Semma; Ni Made Suwitri Parwati; Andi Chairil Furqan (LP2M IAIN Palopo, 2026)
This study aims to examine the effect of market value and leverage on stock prices of manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Market value is proxied by Earnings Per Share (EPS), while leverage is measured using the Debt to Equity Ratio (DER). This research employs a quantitative approach with a causal design and utilizes variance-based Structural Equation Modeling (SEM) through WarpPLS 7.0. The population consists of 219 manufacturing companies, with a sample of 74 firms selected using purposive sampling. The data used are secondary data derived from annual financial statements and year-end closing stock prices. The results indicate that market value, as measured by EPS, has a positive and significant effect on stock prices. This finding suggests that higher profitability per share increases investor interest, thereby driving stock price growth. In contrast, leverage, as proxied by DER, shows a positive but statistically insignificant effect on stock prices. This implies that the level of debt usage is not a primary determinant of stock price movements in manufacturing firms. This study highlights that investors tend to prioritize profitability signals over capital structure in making investment decisions. The findings are expected to provide insights for investors and corporate management in understanding fundamental factors influencing stock prices.